ANALISIS HISTORIS TENTANG SUFISME AL-GHAZÄ€LÄª - Salahuddin, Salahuddin (Hunafa: Jurnal Studia Islamika, 2010)
Al-GazÄlÄ« is viewsÂ  as a figure who succeeded to reconciled between Â the Shari'a with Sufism, and it was he who succeeded to make the teaching of sufism be accepted by the fiqh ulamahis Â (scholars of Fiqh). Sufism is the final Â path which he chose before which heÂ  intensely studied the sensory sciences, theology, and philosophy. It was in Sufism, according to him, that he found the true knowledge which comes from the Creator.Kata Kunci: analisis sufisme. Al-Ghazali, syariat, tasawuf